Older Workers in Transition : European Experiences in a Neoliberal Era - Horst, Mariska van der; Vickerstaff, Sarah, 1956-; Lain, David (Rethinking work, ageing and retirement., 2022)
More people are extending their working lives through necessity or choice in the context of increasingly precarious labour markets and neoliberalism. This book goes beyond the aggregated statistics to explore the lived experiences of older people attempting to make job transitions. Drawing on the voices of older workers in a diverse range of European countries, leading scholars explore job redeployment and job mobility, temporary employment, unemployment, employment beyond pension age and transitions into retirement. This book makes a major contribution and will be essential reading within a range of disciplines, including social gerontology, management, sociology and social policy.